0 votes
32 views
in Complex Numbers by (33.3k points)
closed by

Solve the following quadratic equation:

x2 - (3√2 + 2i) x + 6√2 i = 0)

1 Answer

+2 votes
by (33.2k points)
selected by
 
Best answer

Given equation is x2 – (3√2 + 2i) x + 6√2 i = 0

Comparing with ax2 + bx + c = 0, we get

a = 1, b = -(3√2 + 2i), c = 6√2i

Discriminant = b2 – 4ac

= [-(3√2 + 2i)]2 – 4 × 1 × 6√2 i

= 18 + 12√2i + 4i – 24√2 i

= 18 – 12√2 i – 4 ……[∵ i = -1]

= 14 – 12√2 i

So, the given equation has complex roots.

These roots are given by

Equating real and imaginary parts, we get

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

...